PELAKSANAAN INVENTARISASI ASET DAERAH DI PROVINSI RIAU (Studi kasus di Badan Pengelola Keuangan dan Aset Daerah Provinsi Riau) - Rosita Rosita; Zulkarnaini Zulkarnaini (Journal Publicuho, 2021)
this study aims to determine how the implementation is inventory of regional assets in the regional financial and asset management agency of Riau province, and to find out what are the obstacles in the implementation of the asset inventory, The theory used in this study was the Asset Inventory by Sugiama in Muthiah Sangadji using 3 indicators (Data Collection, Recording, and Reporting). To be able to answer these problems the researcher used a qualitative method with a descriptive approach / in this qualitative research the writer used data collection techniques in the form of observation, Interviews and documentation then analyzed based on the research problem. The results of this study indicate that the implementation of the Regional Asset Inventory at the Regional Financial and Asset Management Agency of Riau Province, Seen from the 3 indicators (Data Collection, Recording and Reporting) has not been carried out properly because there are still deficiencies in controlling activities such as the implementation of the merging of inventory cards and there are still delays in making report. The constraints in this study are the lack of human resources, The method of data collection of assets is not optimal, and not yet orderly in administration.